The old rules no longer apply: explaining Narco-assassinations of Mexican politicians = Las viejas reglas ya no se aplican: explicando los Narco-asesinatos de los políticos Mexicanos - Blume, Laura Ross (2017)
Between 2005 and 2015, organized criminal groups murdered 209 politicians in Mexico. This paper explains why. It argues that the two interwoven trends of political and criminal pluralization in Mexico fostered the conditions for a new type of criminal violence against politicians. Mexican politicians are now targeted for accepting illicit money as well as for standing up to criminals. Moreover, this violence is evidence of an alarming and persistent pattern in Mexico of politicians enlisting criminal organizations to eliminate their political competition. Using a zero-inflated negative binomial model, this paper shows there is a strong statistical relationship between the increase in assassinations and the increases in political pluralization and criminal fragmentation. The article concludes that the failure to protect local public officials creates greater opportunities for the emergence of subnational authoritarian enclaves and threatens democratic consolidation.